2016
DOI: 10.1002/2016ja022642
|View full text |Cite
|
Sign up to set email alerts
|

Small solar wind transients at 1 AU: STEREO observations (2007–2014) and comparison with near‐Earth wind results (1995–2014)

Abstract: This paper discusses small solar wind transients (STs) from 1995 to 2014. Using STEREO data, we have more sites from which to study STs near 1 AU. STEREO measurements are compared with wind observations near the Sun‐Earth line. We examined statistically the dependence of ST occurrence frequency on (i) solar cycle phase, as monitored by the sunspot number (SSN), and (ii) solar wind speed. We find dependencies on both: an anticorrelation with SSN, an opposite trend to that of interplanetary coronal mass ejection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 58 publications
8
50
0
Order By: Relevance
“…Rouillard et al (2010aRouillard et al ( , 2010b demonstrated the tracking of blobs all the way to their in situ detection at 1 au in combined STEREO observations; the authors showed that these blobs were associated, in in situ measurements, to the passage of kinks and loops that were likely part of magnetic flux ropes. Similar transient structures had previously been detected in in situ measurements alone (e.g., Crooker et al 1996Crooker et al , 2004Kilpua et al 2009;Yu et al 2016). More recently, Plotnikov et al (2016) mapped blob emission along the ecliptic plane over nearly a complete solar cycle.…”
Section: Introductionsupporting
confidence: 84%
“…Rouillard et al (2010aRouillard et al ( , 2010b demonstrated the tracking of blobs all the way to their in situ detection at 1 au in combined STEREO observations; the authors showed that these blobs were associated, in in situ measurements, to the passage of kinks and loops that were likely part of magnetic flux ropes. Similar transient structures had previously been detected in in situ measurements alone (e.g., Crooker et al 1996Crooker et al , 2004Kilpua et al 2009;Yu et al 2016). More recently, Plotnikov et al (2016) mapped blob emission along the ecliptic plane over nearly a complete solar cycle.…”
Section: Introductionsupporting
confidence: 84%
“…The imaging observations may provide direct evidences, but this method is generally based on appropriate conditions (such as SFRs should be entrained by corotating interaction regions; e.g., Rouillard et al, , ), which may reduce the accuracy. Several studies investigated the source regions of SFRs using in situ characteristics (e.g., Cartwright & Moldwin, ; Feng & Wang, ; Feng et al, ; Janvier et al, ; Tian et al, ; Yu et al, , ); however, they generally relied on statistical results. Consequently, it is difficult to identify the source region of a specific SFR without sufficiently utilizing the compositional signatures of individual SFRs.…”
Section: Observation and Discussionmentioning
confidence: 99%
“…MCs are of great interest due to their associations with strong solar eruptions and potentially immense geoeffectiveness (e.g., H. Hu et al, ; Wang, Zhang, et al, ). SFRs contribute mainly to slow solar wind, and their source regions and formation mechanisms are still under discussion (e.g., Feng et al, , ; Janvier et al, , ; Kilpua et al, ; Tian et al, ; Yu et al, , ; Zheng & Hu, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large‐scale MCs, which have been thoroughly studied, are associated with strong solar eruptions and drive major space weather events [e.g., Lawrance et al , ; Liu et al , ]. The origins of SFRs and their contributions to the slow solar wind have attracted much attention in recent years [ Moldwin et al , ; Kilpua et al , ; Rouillard et al , ; Feng et al , ; Yu et al , , ].…”
Section: Introductionmentioning
confidence: 99%